2010
DOI: 10.1080/07315724.2010.10719896
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lutein Response Is Greater from Free Lutein Than from Esterified Lutein during 4 Weeks of Supplementation in Healthy Adults

Abstract: These results suggest that the relative serum lutein response will be significantly greater from supplements containing free lutein than from supplements containing lutein esters. These findings should be useful for future clinical trials exploring the effectiveness of lutein supplementation in the prevention of or protection against age-related macular degeneration and/or cataracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…This relation has been previously reported by Norkus et al (55) who observed that higher initial (baseline) serum lutein concentrations predicted greater serum lutein responses after lutein supplementation. This effect suggests that the ability to respond to dietary lutein is a key factor that governs blood and likely tissue lutein concentrations.…”
Section: Discussionsupporting
confidence: 86%
“…This relation has been previously reported by Norkus et al (55) who observed that higher initial (baseline) serum lutein concentrations predicted greater serum lutein responses after lutein supplementation. This effect suggests that the ability to respond to dietary lutein is a key factor that governs blood and likely tissue lutein concentrations.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, Norkus et al. () reported that the serum lutein response was higher with free lutein than with lutein esters. Few reports have been published about the response of the MPOD levels to lutein supplementation compared with each type of lutein (Landrum et al.…”
Section: Introductionmentioning
confidence: 88%
“…Due to the solubility characteristics of carotenoids, the amount of fat consumed in conjunction with carotenoids appears to be an important factor in determining their bioavailability [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…While several single-dose, comparative pharmacokinetic (PK) studies have been conducted in human subjects using lutein or lutein esters [1113], only one multiple-dose PK study [14] has been published. No comparative PK studies using two different sources of unesterified lutein have been published so far.…”
Section: Introductionmentioning
confidence: 99%